2018
DOI: 10.3390/nano8090692
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Magnetic Properties of Large Diameter Co Nanowires and Nanotubes

Abstract: A comparative study of the magnetic properties of the arrays of Co nanowires and nanotubes with large external diameters (180 nm) has been carried out. The nanowires/nanotubes were grown by electrodeposition into the self-assembled pores of anodic alumina membranes. The experimental study of their magnetic behavior was focused on the angular dependence of hysteresis loops and their parameters. In both nanowire and nanotube arrays, from the analysis of experimental data, effective longitudinal magnetic anisotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…167) were 1.19 kOe and 0.81, respectively. The maximum H c (1.88 kOe) of the Co nanowire arrays obtained in the present study is much greater than that in the reference data reported by other researchers [4,5,8,19,20,21,29,30,31]. This large coercivity in the present study was enhanced by the extremely large aspect ratio of ca.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…167) were 1.19 kOe and 0.81, respectively. The maximum H c (1.88 kOe) of the Co nanowire arrays obtained in the present study is much greater than that in the reference data reported by other researchers [4,5,8,19,20,21,29,30,31]. This large coercivity in the present study was enhanced by the extremely large aspect ratio of ca.…”
Section: Resultscontrasting
confidence: 77%
“…Fernandez-Roldan et al investigated the ferromagnetism of Co nanowires and nanotubes with large diameters ( D : 180 nm) that were electrochemically grown in the AAO templates synthesized by hard anodization at 140 V [29]. They discovered that the H c and M r / M s of Co nanowire arrays ( D : 180 nm, L : 6 µm and L / D : ca.…”
Section: Resultsmentioning
confidence: 99%
“…the length, the inner radius and the outer radius. Various experiments [33][34][35][36][37] and theoretical studies [38][39][40][41] based on nanotubes have also show that this structure has great influence on material properties. More recently, Wang et al reported the current-induced skyrmion motion on magnetic nanotubes [42].…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, low dimensional Py structures, such as nanowires (NWs), can afford novel properties compared to 3-D atomic arrangements. As well, one-dimensional ferromagnetic wires display small size effects and a large shape anisotropy 14 , 15 . Therefore, the strategy of decorating a carbonaceous matrix with such nanostructures that reveal a strong dependence on geometrical parameters, like diameter and length 16 , 17 , supplies a key tool to design, tune and control the physical properties of composite materials for high-impact technology 18 20 , with ever-widen utilities, in order to obtain enhanced multiplexed attributes.…”
Section: Introductionmentioning
confidence: 99%